2015
DOI: 10.1186/s40200-015-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression among subjects with and without gestational diabetes mellitus in Bangladesh: a hospital based study

Abstract: BackgroundData on association between depression and diabetes during the pregnancy period in Asia, specifically in Bangladesh are scarce. The study was designed to measure the prevalence of depression during pregnancy with or without Gestational Diabetes Mellitus (GDM).MethodsSeven hundred and forty eight pregnant women (382 with GDM, 366 without-GDM) attending at the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders, participated in the study. Blood glucose was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 32 publications
(42 reference statements)
1
64
2
Order By: Relevance
“…Edinburgh Postnatal Depression Scale (EPDS) was the most frequently used screening tool reported in 17 studies 26 27 29 30 32 34 35 37 40 42 43 47–49 51 53 54. Other tools included Beck Depression Inventory (BDI),41 Hospital Anxiety Depression Scale (HADS),28 38 44 45 56 the Aga Khan University Anxiety Depression Scale (AKUADS),46 55 Kessler Psychological Distress Scale (K-10),25 39 the Montogomery and Asberg Depression Rating Scale (MADRS),36 Hamilton Depression Scale (HAM-D),50 57 Centre for Epidemiological Studies—Depression (CES-D) Scale,52 Patient Health Questionnaire (PHQ-9)33 and Depression Anxiety Stress Scale (DASS-42) 31. There were variations in the threshold scores for identifying antenatal depression both among the tools used and among the studies that used the same tool.…”
Section: Resultsmentioning
confidence: 99%
“…Edinburgh Postnatal Depression Scale (EPDS) was the most frequently used screening tool reported in 17 studies 26 27 29 30 32 34 35 37 40 42 43 47–49 51 53 54. Other tools included Beck Depression Inventory (BDI),41 Hospital Anxiety Depression Scale (HADS),28 38 44 45 56 the Aga Khan University Anxiety Depression Scale (AKUADS),46 55 Kessler Psychological Distress Scale (K-10),25 39 the Montogomery and Asberg Depression Rating Scale (MADRS),36 Hamilton Depression Scale (HAM-D),50 57 Centre for Epidemiological Studies—Depression (CES-D) Scale,52 Patient Health Questionnaire (PHQ-9)33 and Depression Anxiety Stress Scale (DASS-42) 31. There were variations in the threshold scores for identifying antenatal depression both among the tools used and among the studies that used the same tool.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 28 studies included only women with GDM[20,23,26-29,31,33,35-38,40,43-45,47-49,51-53,57,58,60,61,63,64], 14 included women with either GDM or pre-existing diabetes (although the type was not always reported)[22,25,39,41,42,46,50,54-56,59,62,65,66], one included women with either GDM or type 1 diabetes[34], one included only women with type 1 diabetes[67], one included only women with pre-existing diabetes (type not reported)[30] and three did not report the type of diabetes[21,24,32] (Tables 1-3, Supplementary Table 1). Sample sizes ranged from 36[65] to more than 32 million in a retrospective analysis of a nationwide hospital database[22] (Tables 1-3, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations